Reviewing the reviews: the Global Compacts' added value in access to asylum procedures and immigration detention - Atak, Idil; Grundler, Maja; Endres de Oliveira, Pauline; Bast, Jurgen; Guild, Elspeth; Maple, Nicholas; Vanyoro, Kudakwashe; Wessels, Janna; Zyfi, Jona (Frontiers in Human Dynamics, 2023)
This is a provisional file, not the final typeset article in which the treatment of refugees and migrants stands to be improved through the GCs' provisions: (i) use of immigration detention and (ii) access to the asylum procedure, with access to healthcare as a cross-cutting issue. The article discusses how the Compacts' review mechanisms could be improved and theirto utilize the added value of the Compactsin terms of with a view to their impact on domestic migration policies. It argues that both Compact review and implementation can be improved through increased civil society participation.